Beyond fusion: A novel role for ERVW-1 in trophoblast proliferation and type I interferon receptor expression. (August 2022) - C.West, Rachel; Ezashi, Toshihiko; B.Schoolcraft, William; Yuan, Ye
Abstract: Introduction: Throughout human pregnancy there is a delicate balance between the maintenance of a proliferative, trophoblast stem cell pool (TSC) and the differentiation from TSC to placental cell sub-lineages like the syncytiotrophoblast (STB). The STB is comprised of multinucleated cells that come into direct contact with maternal blood and provides the first line of defense to protect the fetus from maternal infections. The differentiation of TSC towards STB is primarily driven by human endogenous retroviruses (HERV), specifically Syncytin-1 (ERVW-1) and Syncytin-2 (ERVFRD-1). Beyond cell fusion, there is also evidence to suggest they can regulate cell proliferation and an antiviral response in other cell types. Therefore, we hypothesized that HERV can regulate cell proliferation as well as an antiviral response in TSCs. Method: shRNA was used to knockdown ERVW-1 in TSCs and revealed reduction in cell proliferation, differentiation, and cell fusion. RT-qPCR and flow cytometry was used to measure other HERV and the presence of Type I and Type II interferon receptors. Results: ERVW-1 knockdown (KD) TSCs had a significantly longer cell doubling time and reduced expression of the proliferation marker Ki67. ERVW-1 KD cells also demonstrated a marked deficiency in the ability to differentiate. Interestingly, ERVFRD-1 was upregulated in both ERVW-1 KD TSC and STB cells compared to controls. Finally, we found that the Type I interferon receptors, IFNAR1 and IFNAR2 were significantly increased in ERVW-1 KD STB cells. Discussion: These findings uncover critical HERV functions in the trophoblasts and a novel role for ERVW-1 during early human placental development. Highlights: ERVW-1 is present in undifferentiated, trophoblast stem cells. Knockdown of ERVW-1 in trophoblast stem cells caused decreased cell proliferation. Type I interferon receptor gene expression was affected by loss of ERVW-1.